2013
DOI: 10.3390/rs5031439
|View full text |Cite
|
Sign up to set email alerts
|

Chromophoric Dissolved Organic Matter and Dissolved Organic Carbon from Sea-Viewing Wide Field-of-View Sensor (SeaWiFS), Moderate Resolution Imaging Spectroradiometer (MODIS) and MERIS Sensors: Case Study for the Northern Gulf of Mexico

Abstract: Empirical band ratio algorithms for the estimation of colored dissolved organic matter (CDOM) and dissolved organic carbon (DOC) for Sea-viewing Wide Field-of-view Sensor (SeaWiFS), Moderate Resolution Imaging Spectroradiometer (MODIS) and MERIS ocean color sensors were assessed and developed for the northern Gulf of Mexico. Match-ups between in situ measurements of CDOM absorption coefficients at 412 nm (a CDOM (412)) with that derived from SeaWiFS were examined using two previously reported reflectance band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Its light absorption coefficient decays almost exponentially, from high absorption coefficients in the ultra-violet to close to zero towards red spectral range [5,6]. A strong near-linear negative correlation between CDOM absorption and salinity has been observed in most shelf sea studies [7,8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Its light absorption coefficient decays almost exponentially, from high absorption coefficients in the ultra-violet to close to zero towards red spectral range [5,6]. A strong near-linear negative correlation between CDOM absorption and salinity has been observed in most shelf sea studies [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…It is presumed that perceived color of seawater in the NWES is strongly driven by CDOM and SPM although chl-a plays a seasonal and local role for example in the Central North Sea [32][33][34][35]. In situ station (blue dots) sampling was done in the German Bight (1)(2)(3)(4)(5)(6)(7)(8), North Sea (9-26), Inner Seas (27)(28)(29)(30)(31)(32)(33)(34), Irish Sea (35)(36)(37)(38)(39)(40)(41)(42)(43), and Celtic Sea (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Region naming is based on maps from The Germany Federal Maritime and Hydrographic Agency [34] and International Hydrographic Organization [35].…”
Section: Study Areamentioning
confidence: 99%
“…The response is always associated with extreme wave heights, large current velocities, and substantial water level variations (Allahdadi et al [1]). Furthermore, tropical cyclones substantially contribute to transport of sediments and biogeochemical substances over oceanic and shelf waters (D'Sa et al [2]; Tehrani et al [3]; Chiaichtehrani [4]). Wave characteristics are among the most relevant oceanic responses of these storms, due to their destructive effects on structures and coastal communities as well as their substantial effects on transport phenomena in the shelf waters.…”
mentioning
confidence: 99%
“…In 2009 this procedure was not available at the laboratories which performed the water sample analysis. Many studies have reported a correlation greater than 0.9 between CDOM and DOC for marine systems [46][47][48][49]. For freshwaters, good correlation between CDOM and DOC was found by [50][51][52][53][54]; however, on the other hand, some studies reported a weaker relationship [55][56][57].…”
Section: Linking the Chemical And Optical Properties Of The Sampled Wmentioning
confidence: 93%